Autonomous Vehicles: How Will They Challenge Law Enforcement? - Cowper, Thomas J.; Levin, Bernard H. (FBI Law Enforcement Bulletin, 2018)
The article focuses on the significant implications for law enforcement concerning the adoption of autonomous vehicles (AV). Topics discussed include efforts of Society of Automotive Engineers International in developing a system for classifying automated driving into various levels; adoption of the developed system by the U.S. National Highway Traffic Safety Administration; and mentions that the AVs has to be programmed that way so that it obeys traffic laws.